An investigation of the barriers to implementing effective logistics strategies in pharmaceutical companies in Zimbabwe. - Manhanga, F. L. (BUSE, 2023)
This study investigated the barriers to implementing effective logistics strategies in pharmaceutical companies. Top on the priority list of any healthcare system is the delivery of drugs as a planned outcome. In the current setting of a health-conscious culture, organization of pharmaceutical supply chains becomes more complicated since it involves the saving of human lives and it therefore requires the participation of various stakeholders that include regulatory agencies, customers, wholesalers, pharmaceutical manufacturers, information service providers and distributors. Pharmaceutical supply chain studies are very limited. The main players in the supply chain of medicines are pharmaceutical companies who are susceptible to numerous risks. Risks inherent in the pharmaceutical chain affect the quality and quantity of the supplies of drugs, which in turn impacts their delivery to customers on time and to the right place. The study objectives were to identify requirements and expectations of customers/end users of pharmaceutical products, to find out measures that have been put in place to improve the movement and distribution of pharmaceuticals by pharmaceutical companies and come up with recommendations for improving the supply chain of pharmaceutical products. The results of this are based on the results of a literature review, obtaining expert opinions and a qualitative system to an improve understanding of the problem. This research will play a pivotal role in exploring the barriers that the supply chain of pharmaceuticals faces and the changing nature of the factors in the PSC that have a special role to play. The study made use of both the quantitative and qualitative approaches and employed a descriptive survey research design. Self-administered questionnaires were distributed to 20 senior logistics officers, 20 supply chain advisors and 8 logistics advisors using simple random and purposive sampling respectively. A total of 20 interviews were conducted with logistics officers, supply chain advisors and logistics advisors. The first step towards this goal is several semi-structured interviews with experts in supply chain management to explore the main challenges. The study found out that the logistics strategies that were used were inventory and return management, efficient transportation through digitisation, warehouse management, dependable suppliers, and operating expenses control. The most significant problems of PSC are inaccuracy in forecasts, long lead times, lack of optimal target stocks and high SC costs. Finally, strategic principles that are recommended include: working with suppliers, investing in new technologies, training, and development programs on logistics to improve organisational performance and establishing information technology (IT). The results can thus give PSC managers a comprehensive view of decision-making and alert them to the importance of the feedback behavior of variables in the long term and their influence on organizational v decisions and goals. It was suggested that a further study be conducted on an expanded area of the health care supply chain with a bigger sample size to enhance the generalisability of the study findings
Keywords: Logistics strategies; Pharmaceutical companies; Pharmaceutical products; Supply chain